The hairdresser of Harare - Huchu, Tendai, 1982- (2011)
"Vimbai is the best hairdresser in Mrs. Khumalo's salon, and she is secure in her status until the handsome, smooth-talking Dumisani shows up one day for work. Despite her resistance, the two become friends, and eventually, Vimbai becomes Dumisani's landlady. He is as charming as he is deft with the scissors, and Vimbai finds that he means more and more to her. Yet, by novel's end, the pair's deepening friendship - used or embraced by Dumisani and Vimbai with different futures in mind - collapses in unexpected brutality. The novel is an acute portrayal of a rapidly changing Zimbabwe. In addition to Vimbai and Dumisani's personal development, the book shows us how social concerns shape the lives of everyday people."--provided by publisher.
Keywords: Beauty operators -- Fiction; Beauty operators -- Fiction; Beauty operators; Harare (Zimbabwe) -- Fiction; Zimbabwe -- Fiction; Zimbabwe; Zimbabwe -- Harare; Fiction